Reversible Functionalization of Clickable Polyacrylamide Gels with Protein and Graft Copolymers. (26th August 2020) - Neira, Hector D.; Jeeawoody, Shaheen; Herr, Amy E.
Abstract: Modular strategies to fabricate gels with tailorable chemical functionalities are relevant to applications spanning from biomedicine to analytical chemistry. Here, the properties of clickable poly(acrylamide‐co‐propargyl acrylate) (pAPA) hydrogels are modified via sequential in‐gel copper‐catalyzed azide‐alkyne cycloaddition (CuAAC) reactions. After optimization, in‐gel CuAAC reactions proceed with rate constants of ≈0.003 s −1, ensuring uniform modifications for gels <200 μm thick. Using the modular functionalization approach and a cleavable disulfide linker, pAPA gels are modified with benzophenone (BP) and acrylate groups. BP groups allow gel functionalization with unmodified proteins using photoactivation. Acrylate groups enable copolymer grafting onto the gels. To release the functionalized unit, pAPA gels are treated with disulfide reducing agents, triggering ≈50% release of immobilized protein and grafted copolymers. The molecular mass of grafted copolymers (≈6.2 kDa) is estimated by monitoring the release process, expanding the tools available to characterize copolymers grafted onto hydrogels. Investigation of the efficiency of in‐gel CuAAC reactions revealed limitations of the sequential modification approach, as well as guidelines to convert the singly functional pAPA gels into gels with three distinct functionalities. Taken together, this modular framework to engineer multifunctional hydrogels benefits application of hydrogels in drug delivery, tissue engineering, and separation science. Abstract : A modular framework to prototype multifunctional hydrogels for applications in drug delivery, tissue engineering, and separation science. Starting with clickable copolymer gels of acrylamide and propargyl acrylate (pAPA gels), new chemical functionalities are imparted via sequential in‐gel click reactions. Using this flexible hydrogel engineering strategy, pAPA gels are reversibly functionalized with unmodified proteins and graft copolymers.